Effects of quercetin and catechin on blood lactate level - Miyaç Göktepe, Meral; Göktepe, Mehmet; Durukan, Erdil; Günay, Mehmet; Güder, Ferhat; Eraslan, Meriç (Progress in Nutrition, 2020)
Study Objectives: This study was aimed to investigate the effects of combined administration of Catechin and Quercetin on blood lactate level. Methods: The research was conducted on 12 male Wistar rats weighing 300-350 gr. Rats were divided into two groups as the control group (n=6) and the test group (n=6). After the rats were quarantined for 10 days; each rat heart blood was taken on the first test day (pre catechin+quercetin supplementation), and again after they were participated to exercise on the second test day (pre catechin+quercetin supplementation). Between days 3 and 12 after testing (for 10 days), each rat in the test group was given 20 ml/kg of catechin+quercetin once daily, and each rat in the control group was given 1ml/kg of 0.05% Dimethyl Sulfoxide (DMSO) by gavage. On days 13 (post catechin+quercetin supplementation), each rat was participated to exercise and take their heart blood. On day 14, the animals were allowed to rest and on day 15 (post catechin+quercetin supplementation), rats’ heart blood were taken under anesthesia. Mann Whitney test was used to analyze data. Results: There was no significant difference between control and test groups during the rest day and during exercise (day 2) testing. Significant changes were observed according to the results of the rats, which were practiced to exercise after administration of catechin+quercetin for 10 days, between day 3 and day 12 after testing. A significant reduction was determined in lactate levels (p